633 Squadron : Operation Rhine Maiden - Smith, Frederick E. (Frederick Escreet), 1922- (Corgi, 1976)
Autumn 1943: an angry American press has blamed the RAF for heavy US B-17 losses over Europe. To restore confidence, joint Allied operations are planned by RAF and 8th Air Force top brass. 663 Squadron, whose Rhine Maiden mission success has won them a glorious reputation is called in to launch Operation Crucible. It is to be a Dieppe-style landing be the Americans, supported by the aces of 633 Squadron. Their hazardous role: to give ground support to troops against overwhelming firepower and totally unforseen odds.